2007
DOI: 10.1099/mic.0.2007/009332-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Paracoccidioides brasiliensis yeast-phase cells recovered from infected mice brings new insights into fungal response upon host interaction

Abstract: Paracoccidioides brasiliensis is a fungal human pathogen with a wide distribution in Latin America. It causes paracoccidioidomycosis, the most widespread systemic mycosis in Latin America. Although gene expression in P. brasiliensis had been studied, little is known about the genome sequences expressed by this species during the infection process. To better understand the infection process, 4934 expressed sequence tags (ESTs) derived from a non-normalized cDNA library from P. brasiliensis (isolate Pb01) yeast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 37 publications
3
58
0
2
Order By: Relevance
“…Our in silico subtractive analysis indicated that the cycle is up-regulated in yeast cells during liver infection, relative to in vitro cultured yeast cells, as demonstrated by the over-expression of the regulatory enzyme isocitrate lyase (Costa et al 2007). This gene is up-regulated in C. albicans during growth inside macrophages (Lorenz & Fink 2001).…”
Section: Preferential Metabolic Pathways That Are Over-induced Duringmentioning
confidence: 99%
See 4 more Smart Citations
“…Our in silico subtractive analysis indicated that the cycle is up-regulated in yeast cells during liver infection, relative to in vitro cultured yeast cells, as demonstrated by the over-expression of the regulatory enzyme isocitrate lyase (Costa et al 2007). This gene is up-regulated in C. albicans during growth inside macrophages (Lorenz & Fink 2001).…”
Section: Preferential Metabolic Pathways That Are Over-induced Duringmentioning
confidence: 99%
“…Of special note, and corroborating our data, the predominance of glycolytic metabolism in Candida albicans infecting mouse kidney (Barelle et al 2006) has been described. The over-expression of carbohydrate metabolism enzymes and overproduction of ethanol suggest that this metabolic pathway could be particularly relevant during liver infection because of the abundant glucose in the host milieu, as described by Costa et al (2007). The abundance of carbohydrate and energy in this infection condition could also pertain to the over-expression of transcripts encoding lipid-biosynthesis enzymes.…”
Section: Preferential Metabolic Pathways That Are Over-induced Duringmentioning
confidence: 99%
See 3 more Smart Citations